Biofuel finance: global trends in biofuel finance in forest-rich countries of Asia, Africa and Latin America and implications for governance - Gelder, J.W. van; German, L. (Center for International Forestry Research, 2011)
Since 2000, US$ 2.0-2.7 billion has been invested in feedstock cultivation for biofuel in 16 forest-rich countries, mostly in oil palm and sugarcane. An additional US$ 5.7-6.7 billion has been invested in biofuel production, especially sugar-based ethanol. While investments in some countries are driven by domestic policies to reduce fossil fuel imports, most are export driven. Sugar-based ethanol offers more opportunities to capture value added than biodiesel feedstocks which are amenable to export and processing abroad. Financing sources for biofuel and related feedstock investments are very diverse, involving domestic and foreign entrepreneurs, state-owned companies, government agencies, public and private banks and institutional investors. Foreign investors play an important role in most forest-rich countries, especially in Africa. To sustain growing demand, significant amounts of new investment are anticipated. Most investors are not yet effectively addressing sustainability challenges in the biofuel sector because they lack responsible investment policies or they are insufficiently robust. Only a few banks have developed responsible investment policies specifically on biofuels. The private financial sector has not yet followed multilateral financial institutions in creating mediation procedures to address grievances of people harmed or potentially harmed by projects financed by their institutions. Responsible investment instruments in the biofuel sector need to be based on an internationally agreed set of principles, criteria and indicators which are measurable, reportable and verifiable; should be applied to all forms of private and public finance provided to all companies in the supply chain; and should be strengthened by independent compliance and monitoring processes. Governments should stimulate and support private financial institutions to develop and apply sound responsible investment policies and instruments.